Pandemic Covid-19, Revolution Industry 4.0 and Digital Entrepreneur Trending - Annisa Hakim Zamzami; Febrina Mahliza; Anees Janee Ali; Lucky Nugroho (Universitas Mercu Buana, 2022)
Change is an inevitability where currently the business world is exposed to the Covid-19 Pandemic, Industrial Revolution 4.0. Therefore, this study aims to analyze the needs of the majority of society today and how entrepreneurs can survive and expand their businesses in an era of volatility, uncertainty, complexity, and ambiguity. Referring to the purpose of the research, the formulation of this research problem includes: (i) What are the characteristics of consumers of the Gen Z group and millennials?; (ii) What are the challenges for entrepreneurs in the era of the Covid-19 Pandemic, the VUCA era and the era of the Industrial Revolution 4.0?; (iii) How can entrepreneurs retain the consumers in the era of the Covid-19 Pandemic, the VUCA era and the era of the Industrial Revolution 4.0?, the VUCA era and the era of the Industrial Revolution 4.0?. Furthermore, the results of this study are that the majority of the composition of the current population of Indonesia is Gen Z and Millennials. Therefore, they need digital-based products and services so that entrepreneurs can capture these needs and turn business processes and business models into digital entrepreneurs. Therefore, the implication of this research is to provide information to entrepreneurs and all stakeholders related to the field of entrepreneurship. In addition, the novelty of this research is to connect the needs of the majority of society at this time with digital entrepreneurs